Family Hope Program (PKH) in Providing Family Welfare in Selagalas Village, Indonesia. - Ihsan Rois; Annisa Prina Wulandari (Experimental Student Experiences, 2023)
This study aims to determine the implementation of the Family Hope Program (PKH) in providing family welfare in Selagalas Village, Sandubaya District, Mataram City. The research approach used is a qualitative approach with data collection techniques, observation, interviews, and documentation. Maintenance of informants in this study used snowball and purposive techniques. The informants from this study consisted of 1 key informant, 3 main informants, and 6 additional informants. The technique of checking the validity of the data used by the authors in this study is to use triangulation techniques (source triangulation, method triangulation, and theoretical triangulation). Based on the results obtained from the research the implementation of the PKH program in Selagalas Village has not run optimally, this can be seen from the main objectives of the PKH program in reducing poverty, breaking the poverty chain and improving the quality of human resources which have not been achieved